2010
DOI: 10.3382/ps.2009-00244
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physicochemical properties of egg white and yolk proteins from duck shell eggs due to hydrostatic pressure treatment

Abstract: The shell of the duck egg did not crack after pressure treatments (300 to 500 MPa; 25 degrees C; 10 min) in this study; therefore, the changes of physicochemical properties of egg white and yolk proteins from the intact shell egg by pressure treatment were first investigated and compared with those of pressurized hen liquid eggs. Although the proximate compositions of duck eggs and hen eggs were similar, the moisture and protein contents of hen whole eggs were higher than those of duck whole eggs. The protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
0
12
0
3
Order By: Relevance
“…For example, pressures above 450 MPa result in loss of the secondary structure of albumin (Hayakawa and others ) and exposure of buried hydrophobic and SH groups (Iametti and others ). Pressures between 400 and 700 MPa can greatly increase the surface hydrophobicity and exposed SH groups in egg white proteins (van der Plancken and others ; Lai and others ). Studies involving hen egg white lysozyme showed that HHP treatment significantly increased the number of partially unfolded forms of the protein (Nash and Jonas ).…”
Section: Impact Of Hhp On Egg Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pressures above 450 MPa result in loss of the secondary structure of albumin (Hayakawa and others ) and exposure of buried hydrophobic and SH groups (Iametti and others ). Pressures between 400 and 700 MPa can greatly increase the surface hydrophobicity and exposed SH groups in egg white proteins (van der Plancken and others ; Lai and others ). Studies involving hen egg white lysozyme showed that HHP treatment significantly increased the number of partially unfolded forms of the protein (Nash and Jonas ).…”
Section: Impact Of Hhp On Egg Componentsmentioning
confidence: 99%
“…Eggs are composed of different proteins with high biological, functional, and nutritional properties, and they are used in numerous food products (Lai and others ). Egg white (albumin) is composed of 9% proteins, 0.03% lipids, 0.9% carbohydrates, 0.05% ash, and 90% water (Awade ).…”
Section: Structural and Functional Modifications Of Hhp‐treated Egg Amentioning
confidence: 99%
“…4.7 , Yan et al 2010 ). Lai et al ( 2010a ) studied the effect of HPTs (300-500 MPa, 25 °C, 10 min) on changes in the physicochemical properties of egg white and yolk proteins of duck eggs. HPT at 500 MPa showed that egg white proteins underwent slight but signifi cant unfolding and aggregation, whereas HPT below 500 MPa induced insignifi cant changes in the physicochemical properties.…”
Section: Eggsmentioning
confidence: 99%
“…Several researches reported the effect of processing parameters on egg albumen protein functionalities. For instances, high‐pressure treatment impaired the solubility of albumen proteins due to protein unfolding and aggregation (Lai et al , ). The outlet air temperature and atomisation pressure conditions of spray drying affected the emulsion stability, gelation and foaming stability of resulting dried whole egg powder (Koç et al , ).…”
Section: Introductionmentioning
confidence: 99%